2022
DOI: 10.1177/00034894221112911
|View full text |Cite
|
Sign up to set email alerts
|

Parental Knowledge of Obstructive Sleep Apnea Symptoms and Tonsillectomy in Children

Abstract: Objective: Obstructive sleep apnea (OSA) is present in approximately 2% to 5% of children; however, only 15% of parents are reported to be knowledgeable about OSA in children. Sleep apnea in children can lead to cardiopulmonary disease, abnormal weight gain, failure to thrive, or learning difficulties. The purpose of our study is to assess parental knowledge of pediatric OSA to identify any knowledge gaps. Study Design: Survey. Setting: Three pediatric otolaryngology clinics associated with a tertiary care chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(40 reference statements)
1
1
0
Order By: Relevance
“…In our study, hyperactivity and bed wetting were the least recognized symptoms among the parents. These results are similar to the findings of DiNardo et al and Bashir et al [10,16]. On the other hand, adenoids and tonsils enlargement, allergic sinusitis, asthma, and obesity were well-recognized risk factors by the parents in our study.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, hyperactivity and bed wetting were the least recognized symptoms among the parents. These results are similar to the findings of DiNardo et al and Bashir et al [10,16]. On the other hand, adenoids and tonsils enlargement, allergic sinusitis, asthma, and obesity were well-recognized risk factors by the parents in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, a recent study conducted by DiNardo et al revealed that parents had a mean score of 6.3 out of 13 for recognizing pediatric OSA symptoms, with nocturnal enuresis and hyperactivity being the least recognized symptoms by 27% and 37% of parents, respectively. The study also showed that parents who expressed greater concern about OSA had a higher cumulative knowledge score [ 12 ]. These results confirm our findings that parents may not be aware of the full range of symptoms associated with OSA, highlighting the importance of educating parents about the full range of symptoms associated with OSA to ensure timely diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%